Assuring quality of teaching and learning in post-conflict higher education: The Case of Somalia - Abukar Mukhtar Omar; Mohamed Ali Osman; Abdirahman Ibrahim Abdi (Cogent Education)
This study examines the factors that contribute to ensuring the quality of teaching and learning in post-conflict higher education in Somalia (1991–present). It examines how the quality of the curriculum, academic staff, and infrastructure impact the quality of teaching and learning. A quantitative research approach was adopted, utilizing a structured questionnaire administered to the academic staff at higher education institutions in Mogadishu. The data were analyzed using the SmartPLS software. This is the first study to integrate Biggs’ 3 P and Resource-Based View frameworks, and empirically quantify these relationships in a Somali post-conflict context. The findings indicated that all three factors had positive and significant impacts on teaching and learning quality, with infrastructure having the most substantial effect. This study recommends strategic investment in infrastructure, dynamic curriculum development, and faculty training. These insights provide valuable guidance for policymakers and academic leaders seeking to rebuild a resilient higher education system.